Handling The Juvenile Delinquency Caused by Consuming Alcohol - Ali Ashadi; Amin Purnawan (Jurnal Daulat Hukum, 2018)
The problem in this research are: 1) The factors that affect juvenile delinquency caused by consuming alcohol 2) The handling of juvenile delinquency caused by consuming alcohol. The purpose of this study were 1) To identify and explainfactors that affect juvenile delinquency caused by consuming alcohol. 2) To identify and explain the handling of juvenile delinquency caused by consuming alcohol.Based on the results of the study concluded that: 1) The factors that influence the habit of drinking in teenagers is a curiosity, social environment, family environment, the influence of alcohol sales freely, and as a result of the rule of law (sanctions and fines lightweight). 2) Disaster of drinking habits in teenagers by the police is divided into two stages: a preventive and repressive. Namely preventive measures, early efforts made by the police to prevent all crimes include socialization, raid the alcohol, and Binamitra (one of strategy in police), while the repressive efforts, action to suppress and restrain delinquency or impede the onset of delinquency greater events include foreclosure, arrest, legal action.Keywords : Handling; Delinquency; Alcohol.